Deteksi Kondisi Hutan Paska Kebakaran Melalui Citra Multisensor MOS-MESSR dan Landsat TM: Studi Kasus di Areal PT. MHP Sumatera Selatan - I Nengah Surati Jaya; Endang Pujiastuti; Muhammad Buce Saleh (Jurnal Manajemen Hutan Tropika, 2000)
This paper presents how the multisensor MOS-MESSR and Landsat Thematic Mapper (TM) should be manipulated as tools for detecting land cover changes. Radiometric correction using image regression was recognized as useful approach to adjust pixel brightness value of MOS-MESSR. In this study, the standardized MPC showed comparable accuracy, similar to DMC method. Using this technique forest changes due to fire as well as land clearing were well recognized. Some recommendations and suggestions for improving classification accuracy of change detection using multisensor MOS-MESSR and Landsat TM were drawn up from this study.